The Impact of Smartphone Adoption on Marketing Therapeutic Tourist Sites in Jordan - Alghizzawi, Mahmoud; Abd. Ghani, Mazuri; Puad Mat Som, Ahmad; Fazil Ahmad, Muhamad; Amin, Aziz; Abu Bakar, Norsuhaily; A. Salloum, Said; Habes, Mohammed (International Journal of Engineering and Technology, 2018)
The aim of the study is to find out the effect of smartphone on marketing therapeutic tourist sites in Jordan. Several factors contribute to this study, including market type templates, therapeutic, demographic and their impact on tourist behavior in Jordan. We apply the technology acceptance (TAM) model to study through the incorporation of smartphone applications on marketing therapeutic tourist sites in Jordan. To achieve this, we use the quantitative research design and rely on appropriate data to test the hypothesis. We distributed questionnaire to 400 tourists as a sample of study but two hundred and four were collected. The researchers had used the structural equation modeling (PLS-SEM) for measuring relationships and correlations between variables and their impact on the behavior of tourists in Jordan. According to the study findings, there was a positive impact on market type template, therapeutic, and demographics on tourists' perceived ease of use of smartphone on marketing therapeutic tourist sites in the country. Perceived usefulness and perceived ease of use also led to an increase in tourists' intention to use smartphone.Â Â